Theoretical framework of predictors volunteering behavior - Nur Husnina; Asmuni, Azizan; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2017)
Youth are human capital used by a nation for a long term investment. Youth play important role in shaping the future of politics, economy and society in Malaysia.Volunteers devoted to their life to help others regardless their time and effort. However, in 2010, the numbers of volunteers dropped significantly. It is important to study what predictors that contribute intention to volunteers among youth. Volunteering is the course of action that individual’s willing to perform without anticipating any payment to help other people, community and organization. Theories that been applied in this research area are Theory of Reasoned Action (TRA), Theory of Planned Behavior (TPB), Integrated Behavioral Model (IBM), and role identity theory. Continued studies of predictors of volunteering behavior can promote participation in volunteering activities.